Laser-induced transfer of gel microdroplets for cell printing. (December 2017) - Yusupov, V.I.; Zhigar'kov, V.S.; Churbanova, E.S.; Chutko, E.A.; Evlashin, S.A.; Gorlenko, M.V.; Cheptsov, V.S.; Minaev, N.V.; Bagratashvili, V.N.
Abstract: We study thermal and transport processes involved in the transfer of gel microdroplets under the conditions of laser cell microprinting. The specific features of the interaction of pulsed laser radiation ( λ = 1.064 µm, pulse duration 4 – 200 ns, energy 2 µJ – 1 mJ) with the absorbing gold film deposited on the glass donor substrate are determined. The investigation of the dynamics of transport processes by means of fast optical video recording and optoacoustic methods makes it possible to determine the characteristics of the produced gel jets as functions of the laser operation regimes. The hydrodynamic process of interaction between the laser radiation and the gold coating with the hydrogel layer on it is considered and the temperature in the region of the laser pulse action is estimated. It is shown that in the mechanism of laser-induced transfer a significant role is played by the processes of explosive boiling of water (in gel) and gold. The amount of gold nanoparticles arriving at the acceptor plate in the process of the laser transfer is determined. For the laser pulse duration 8 ns and small energies (less than 10 µJ), the fraction of gold nanoparticles in the gel microdroplets is negligibly small, and their quantity linearly grows with increasing pulse energy. The performed studies offer a base for optimising the processes of laser transfer of gel microdroplets in the rapidly developing technologies of cell microprinting.